2022
DOI: 10.1039/d2ay00508e
|View full text |Cite
|
Sign up to set email alerts
|

Detection of kerosene adulteration in automobile fuel by a low-loss surface plasmon resonance (SPR) chemical sensor

Abstract: A surface plasmon resonance (SPR) chemical sensor with gold as the sensitive materials is designed to detect adulteration of petrol by kerosene. Samples of petrol adulterated with kerosene were...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 96 publications
0
1
0
Order By: Relevance
“…The sensor components are fused silica, TiO2, and gold coating [15]. Yang et al [16] also reported their work related to the SPR-PCF component in detecting kerosene concentrations in the concentration range of 0% to 90%, in their work obtaining a confinement loss (CL) of 5.4 dB/cm. Nuzhat et al [17] reported ultra-sensitivity SPR-PCF sensor components in detecting the analyte RI, the detection ranges from 1.33 to 1.4 RIU.…”
Section: Introductionmentioning
confidence: 99%
“…The sensor components are fused silica, TiO2, and gold coating [15]. Yang et al [16] also reported their work related to the SPR-PCF component in detecting kerosene concentrations in the concentration range of 0% to 90%, in their work obtaining a confinement loss (CL) of 5.4 dB/cm. Nuzhat et al [17] reported ultra-sensitivity SPR-PCF sensor components in detecting the analyte RI, the detection ranges from 1.33 to 1.4 RIU.…”
Section: Introductionmentioning
confidence: 99%